(untitled) (CIPEEX, 2025)
This study aimed to understand the psychological and emotional impacts of abusive relationships on the mental health of women in situations of financial and emotional dependence. The research was conducted through a systematic review of qualitative nature, analyzing scientific articles published in the last ten years in databases such as SciELO, PubMed, and the CAPES Journals Portal, in addition to official documents related to violence against women. Inclusion criteria considered exclusively the female population and studies addressing gender-based violence and mental health. The results highlighted the main psychological damages experienced by women in abusive relationships, such as depression, anxiety, low self-esteem, social isolation, and feelings of guilt, as well as the factors that hinder the breaking of the cycle of violence, including emotional and financial dependence. The study is justified by the social and academic relevance of the theme, since violence against women constitutes a global public health problem and demands greater visibility of its psychological consequences, contributing to the development of public policies and more effective psychosocial support and intervention strategies.